Evaluation of Calculation Methods used for Estimating the Ultimate Moment Resistance of Bridge Decks Reinforced with FRP Bars - Tomas Skuturna; Juozas Valivonis (The Baltic Journal of Road and Bridge Engineering)
A statistical research of the calculation methods for calculating ultimate moments of concrete elements reinforced with fibre-reinforced plastic is presented. For this purpose a database of experimental results has been collected. Calculations of the ultimate moment resistance were performed according to three design recommendations. Wilk-Shapiro test were used to determine the distribution of experimental and theoretical data. The statistical research to evaluate the calculation methods was performed by testing the statistical hypothesis on the differences between theoretical and experimental values. It is suggested to calculate the coefficient of confidence for assessing the accuracy of calculation methods.